Intercultural communication with Quechua and Aymara students: «Mother water – clean hands, healthy children!» - Lipa Tudela, Frida (2025)
In intervention contexts within indigenous communities, communication faces challenges such as linguistic barriers, cultural differences, and distrust toward external approaches. Overcoming these obstacles requires intercultural strategies that integrate local traditions and promote respectful dialogue to achieve sustainable changes in health habits. In response, a study was conducted to develop an intercultural communication intervention aimed at fostering adherence to handwashing practices among Quechua and Aymara schoolchildren. The methodology employed a mixed-methods approach with a quasi-experimental pretest-posttest design without a control group, involving 16 schoolchildren from Mataro Chico, in Azángaro, and 19 from Luquina Chico, in Chucuito, both located in the Puno region. Pretest results revealed low adherence to handwashing practices. The intervention was designed with songs in native languages and respected the cultural reverence for Mother Water, achieving a significant improvement in adherence after the posttest. The conclusions emphasize that an intercultural approach, respectful of local customs and based on community participation, is essential to ensure adherence to healthy habits in these communities.